2020
DOI: 10.1080/0886022x.2020.1735416
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic characteristics and outcomes of lupus nephritis with positive antineutrophil cytoplasmic antibody

Abstract: Aims: The aim was to determine whether anti-neutrophil cytoplasmic antibody (ANCA)-positive serology in patients with lupus nephritis (LN) is associated with different clinicopathologic features and outcomes. Methods: In our retrospective analysis, 283 patients were enrolled between 2013 and 2018. Thirty-six patients were ANCA-positive, and this group was compared with the remaining 247 patients who were confirmed as ANCA-negative at the time of biopsy. Results: ANCA-positive LN patients exhibited higher anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Some of the ANCAs have been shown to be strongly associated with so-called “pauci-immune” glomerulonephritides due to the absence of deposits of immune complexes within the glomerular tuft [ 151 , 152 ]. In two retrospective studies of Chinese patients with LN, Wang et al explored the clinical relevance of ANCAs in LN [ 153 , 154 ]. In these works, anti-myeloperoxidase (MPO) ANCA was demonstrated to be the most prevalent ANCA in ANCA-positive LN patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the ANCAs have been shown to be strongly associated with so-called “pauci-immune” glomerulonephritides due to the absence of deposits of immune complexes within the glomerular tuft [ 151 , 152 ]. In two retrospective studies of Chinese patients with LN, Wang et al explored the clinical relevance of ANCAs in LN [ 153 , 154 ]. In these works, anti-myeloperoxidase (MPO) ANCA was demonstrated to be the most prevalent ANCA in ANCA-positive LN patients.…”
Section: Resultsmentioning
confidence: 99%
“…In these works, anti-myeloperoxidase (MPO) ANCA was demonstrated to be the most prevalent ANCA in ANCA-positive LN patients. An increased risk of mortality in ANCA-positive LN patients compared with ANCA-negative LN patients was observed both in the first (HR adj = 3.4; p = 0.03 [ 153 ]) and the second study (RR adj = 3.6; p = 0.016 [ 154 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Pauci-immune glomerulonephritis was not reported in another pediatric cohort or adult cohorts of LN with ANCA positivity either. 6,12,21 These inconsistent results emphasized the need of further prospective studies to clarify the relationship between ANCAs and the degree of renal immune deposition in context of LN.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the symptoms of both diseases may present at different times. On the other hand, it has already been reported that 16–42% of SLE cases and 37–53% of LN cases are ANCA positive [ 10 ]. LN patients with ANCA positivity tend to have a higher clinical severity than those without ANCA.…”
Section: Discussionmentioning
confidence: 99%